Decreased Thalamic Activity Is a Correlate for Disconnectedness during Anesthesia with Propofol, Dexmedetomidine and Sevoflurane But Not S-Ketamine - Kantonen, Oskari; Laaksonen, Lauri; Alkire, Michael; Scheinin, Annalotta; Långsjö, Jaakko; Kallionpää, Roosa E.; Kaisti, Kaike; Radek, Linda; Johansson, Jarkko; Laitio, Timo; Maksimow, Anu; Scheinin, Joonas; et al. (The Journal of neuroscience, 2023)
Establishing the neural mechanisms responsible for the altered global states of consciousness during anesthesia and dissociating these from other drug-related effects remains a challenge in consciousness research. We investigated differences in brain activity between connectedness and disconnectedness by administering various anesthetics at concentrations designed to render 50% of the subjects unresponsive. One hundred and sixty healthy male subjects were randomized to receive either propofol (1.7 μg/ml; n = 40), dexmedetomidine (1.5 ng/ml; n = 40), sevoflurane (0.9% end-tidal; n = 40), S-ketamine (0.75 μg/ml; n = 20), or saline placebo ( n = 20) for 60 min using target-controlled infusions or vaporizer with end-tidal monitoring. Disconnectedness was defined as unresponsiveness to verbal commands probed at 2.5-min intervals and unawareness of external events in a postanesthesia interview. High-resolution positron emission tomography (PET) was used to quantify regional cerebral metabolic rates of glucose (CMR glu ) utilization. Contrasting scans where the subjects were classified as connected and responsive versus disconnected and unresponsive revealed that for all anesthetics, except S-ketamine, the level of thalamic activity differed between these states. A conjunction analysis across the propofol, dexmedetomidine and sevoflurane groups confirmed the thalamus as the primary structure where reduced metabolic activity was related to disconnectedness. Widespread cortical metabolic suppression was observed when these subjects, classified as either connected or disconnected, were compared with the placebo group, suggesting that these findings may represent necessary but alone insufficient mechanisms for the change in the state of consciousness. SIGNIFICANCE STATEMENT Experimental anesthesia is commonly used in the search for measures of brain function which could distinguish between global states of consciousness. However, most previous studies have not been designed to separate effects related to consciousness from other effects related to drug exposure. We employed a novel study design to disentangle these effects by exposing subjects to predefined EC 50 doses of four commonly used anesthetics or saline placebo. We demonstrate that state-related effects are remarkably limited compared with the widespread cortical effects related to drug exposure. In particular, decreased thalamic activity was associated with disconnectedness with all used anesthetics except for S-ketamine.